2023
DOI: 10.1088/1361-648x/accd39
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic dopings in epitaxial films MnBi2Te4

Abstract: The intrinsic antiferromagnetic topological insulator MnBi2Te4 and members of its family have been the subject of theoretical and experimental research, which has revealed the presence of a variety of defects and disorders that are crucial in determining the topological and magnetic properties. This also brings about challenges in realizing the quantum states like the quantum anomalous Hall and the axion insulator states. Here, utilizing cryogenic magnetoelectric transport and magnetic measurements, we systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…According to the STM measurements shown in Figures S2, S9, and S10, the grown MBT films acquire island-like surface morphologies and a nonuniform thickness distribution in the nanometer scale. This could induce a net magnetization and discernible AH effects in the fabricated MBT films with a nominal thickness of an even or odd number of SLs, as validated in this work and also in previous reports …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…According to the STM measurements shown in Figures S2, S9, and S10, the grown MBT films acquire island-like surface morphologies and a nonuniform thickness distribution in the nanometer scale. This could induce a net magnetization and discernible AH effects in the fabricated MBT films with a nominal thickness of an even or odd number of SLs, as validated in this work and also in previous reports …”
Section: Resultssupporting
confidence: 87%
“…This could induce a net magnetization and discernible AH effects in the fabricated MBT films with a nominal thickness of an even or odd number of SLs, as validated in this work and also in previous reports. 56 Figures S12 and S13 A (μ 0 H = 0) at zero-field (negative or positive) that is taken after sweeping the magnetic field from 9 to 0 T. Apparently, the polarity of AH loops preserves a negative sign for samples S1−S3, coinciding with the results in previous studies. 39,40,57 The ordinary Hall resistivity ρ yx OH = R H × μ 0 H is proportional to the magnetic field μ 0 H, so the carrier density of samples S1−S3 can be extracted by n H = 1/(R H × q), where R H and q are the Hall coefficient and elementary charge, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The observed hysteresis in 34 SL and 10 SL films (Figures i and d) indicates a net magnetization, which could be induced by the nonuniformity, disorders, or defects over the ∼1.5 mm × 2 mm Hall-bar structure and the substrate-induced top-bottom surface asymmetry . The inevitable defects in MnBi 2 Te 4 have been verified by theoretical calculations and experiments. Compared to 9 SL MnBi 2 Te 4 , the smaller zero-field AHE resistance and spin-flop field of 10 SL are consistent with thickness-dependent RMCD and transport results on exfoliated nanoflakes ,, (Figure S5). It is reported that the quantum anomalous Hall effect with nearly quantized R xy A and quenched R xx can be observed in low-disorder codoped topological insulators (named as quantum anomalous Hall insulators).…”
supporting
confidence: 66%
“…As the Mn Bi concentration is small, MBT still exhibits an overall A-type AFM ground state (i.e., the interlayer AFM interactions are dominant). In MST, due to similar ionic radii of Sb 3+ and Mn 2+ (smaller than that of Bi 3+ ), a higher Mn–Sb antisite concentration (around 15% Mn Sb and 30% Sb Mn ) is reported when compared to the Mn–Bi antisite concentration (around 5% Mn Bi and 20% Bi Mn ) in MBT. ,,, Therefore, as introduced above, these antisite defects exert significant influences on the overall magnetic structures (AFM or FIM) and transition temperatures of MST. ,, In addition to magnetism, the Mn–Bi/Sb antisite defects would also induce electron/hole doping and alter the Fermi surface, band inversion, and topology of Mn­(Sb/Bi) 2 n +2 Te 3 n +4 . Despite the importance of the defects, their formation mechanism, the methods to tune their concentration and distribution, and how they can control the magnetism remain unclear.…”
Section: Introductionmentioning
confidence: 99%